The Development of Cortical Bone Level During the Placement of Dental Implants in Two Surgical Stages Without Mucoperiosteal Flaps - Valentin Topalo; Oleg Dobrovolschi; Dumitru Sirbu; Nicolae Chele; Fahim Atamni (Romanian Society of Oral Rehabilitation, 2010)
The present study has been carried out for a comparative assessment of periimplantory cortical bone level changes during the osteointegration of the dental endosseous implants placed according to the standard method and of those placed without mucoperiosteal flaps. The study included 98 persons. The comparative study showed that the resorption level of the periimplantory cortical bone at implants placement according to the suggested method is veridically less (p < 0,001). The mucoperiosteal flaps cause the bone resorption of the periimplantory bone. This phenomenon can be prevented or reduced by flapless implants placement.